Leopard (Panthera pardus) occupancy in the Chure range of Nepal. Issue 20 (21st September 2021) - Lamichhane, Babu Ram; Lamichhane, Saneer; Regmi, Rajan; Dhungana, Milan; Thapa, Shyam Kumar; Prasai, Anil; Gurung, Aashish; Bhattarai, Santosh; Paudel, Rajan Prasad; Subedi, Naresh
Abstract: Conservation of large carnivores such as leopards requires large and interconnected habitats. Despite the wide geographic range of the leopard globally, only 17% of their habitat is within protected areas. Leopards are widely distributed in Nepal, but their population status and occupancy are poorly understood. We carried out the sign‐based leopard occupancy survey across the entire Chure range ( 19, 000 km 2 ) to understand the habitat occupancy along with the covariates affecting their occupancy. Leopard signs were obtained from in 70 out of 223 grids surveyed, with a naïve leopard occupancy of 0.31. The model‐averaged leopard occupancy was estimated to be 0.5732 ( SE 0.0082) with a replication‐level detection probability of 0.2554 ( SE 0.1142). The top model shows the additive effect of wild boar, ruggedness, presence of livestock, and human population density positively affecting the leopard occupancy. The detection probability of leopard was higher outside the protected areas, less in the high NDVI (normalized difference vegetation index) areas, and higher in the areas with livestock presence. The presence of wild boar was strong predictor of leopard occupancy followed by the presence of livestock, ruggedness, and human population density. Leopard occupancy was higher in west Chure (0.70 ± SE 0.047) having five protected areas compared with east Chure (0.46 ± SE 0.043) with no protected areas. Protected areas and prey species had positive influence on leopard occupancy in west Chure range. Similarly in the east Chure, the leopard occupancy increased with prey, NDVI, and terrain ruggedness. Enhanced law enforcement and mass awareness activities are necessary to reduce poaching/killing of wild ungulates and leopards in the Chure range to increase leopard occupancy. In addition, maintaining the sufficient natural prey base can contribute to minimize the livestock depredation and hence decrease the human–leopard conflict in the Chure range. Abstract : The model‐averaged leopard occupancy in the Chure range ( 19, 000 km 2 ) was 0.5732 ( SE 0.0082) with a detection probability of 0.2554 ( SE 0.1142). The top model included wild boar, ruggedness, presence of livestock, and human population density as covariates. Further, maintaining a sufficient natural prey base can contribute to minimize the livestock depredation and hence decrease the human–leopard conflict in the Chure range.